Toward a Working- Waterfront Ethic: Preserving Access to Maine’s Coastal Economy, Heritage, and Local Seafood - Snyder, Robert (Maine Policy Review, 2011)
Maine has one of the most beautiful coastlines in the world, one for which people are willing to pay a premium. But for Maine fisherman, the coast is how they access their livelihood. In 2002 only 25 miles of Maine’s 5,300-mile coastline supported working-waterfront access. This article discusses creative and innovative strategies to preserve Maine’s working waterfront, including current-use taxation, purchase of development rights, and community-supported fisheries (CSF).